Social Economic Factors, Depression, and Resilience among Women with Breast Cancer in Surakarta - Larasati, Gayatri Kintan; Adriani, Rita Benya; Murti, Bhisma (Indonesian Journal of Medicine, 2018)
Background: Women with breast cancer will experience physical and psychological changes that can cause depression. Social factors related to depression can affect the resilience of breast cancer sufferers. This study aimed to determine the factors that affect depression and resilience in women with breast cancer.Subjects and Method: This was a cross-sectional study conducted in Kerten, Surakarta, from November to December 2018. A total of 200 women was selected for this study using simple random sampling. The dependent variable was the resilience of women with breast cancer. The independent variables were depression, family support, peer support, group support, self-efficacy, and coping mechanism. The data were collected by questionnaire and analyzed by path analysis run on Stata 13.Results: Resilience was directly affected by depression (b= -0.09; 95% CI= -0.14 to -0.05; p <0.001), family support (b = 0.22; 95% CI= 0.11 to 0.32; p<0.001), peer support (b = 0.23 ; 95% CI= 0.12 to 0.34; p <0.001), group support (b= 0.18; 95% CI= 0.06 to 0.29; p= 0.002), self-efficacy (b = 0.15; 95% CI= 0.06 to 0.24; p = 0.001), and coping mechanism (b= 0.05; 95% CI= 0.03 to 0.09; p= 0.001). Resilience was indirectly affected by family support, peer support, group support, and self efficacy.Conclusions: The resilience of women with breast cancer is directly affected by depression, family support, peer support, group support, self-efficacy, and coping mechanism, but it is indirectly affected by family support, peer support, group support, and self-efficacy.Keywords: resilience, breast cancer, depression, support, self-efficacy, the coping mechanismCorrespondence: Gayatri Kintan Larasati. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta, Central Java 57126. Email: gayatrikintanlarasati@gmail.com. Mobile: +6285655084332.Indonesian Journal of Medicine, (2018), 3(2): 110-118https://doi.org/10.26911/theijmed.2018.03.02.07